Neoadjuvant chemotherapy drives intratumoral T cells toward a proinflammatory profile in pancreatic cancer - Max Heiduk; Ioana Plesca; Jessica Glück; Luise Müller; David Digomann; Charlotte Reiche; Janusz von Renesse; Rahel Decker; Christoph Kahlert; Ulrich Sommer; Daniela E. Aust; Marc Schmitz; et al. (JCI Insight, 2022)
BACKGROUND Pancreatic ductal adenocarcinoma (PDAC) has a dismal prognosis. At diagnosis, only 20% of patients with PDAC are eligible for primary resection. Neoadjuvant chemotherapy can enable surgical resection in 30%–40% of patients with locally advanced and borderline resectable PDAC. The effects of neoadjuvant chemotherapy on the cytokine production of tumor-infiltrating T cells are unknown in PDAC.METHODS We performed multiplex immunofluorescence to investigate T cell infiltration in 91 patients with PDAC. Using flow cytometry, we analyzed tumor and matched blood samples from 71 patients with PDAC and determined the frequencies of T cell subsets and their cytokine profiles. Both cohorts included patients who underwent primary resection and patients who received neoadjuvant chemotherapy followed by surgical resection.RESULTS In human PDAC, T cells were particularly enriched within the tumor stroma. Neoadjuvant chemotherapy markedly enhanced T cell density within the ductal area of the tumor. Whereas infiltration of cytotoxic CD8+ T cells was unaffected by neoadjuvant chemotherapy, the frequency of conventional CD4+ T cells was increased, and the proportion of Tregs was reduced in the pancreatic tumor microenvironment after neoadjuvant treatment. Moreover, neoadjuvant chemotherapy increased the production of proinflammatory cytokines by tumor-infiltrating T cells, with enhanced TNF-α and IL-2 and reduced IL-4 and IL-10 expression.CONCLUSION Neoadjuvant chemotherapy drives intratumoral T cells toward a proinflammatory profile. Combinational treatment strategies incorporating immunotherapy in neoadjuvant regimens may unleash more effective antitumor responses and improve prognosis of pancreatic cancer.FUNDING This work was supported by the Jung Foundation for Science and Research, the Monika Kutzner Foundation, the German Research Foundation (SE2980/5-1), the German Cancer Consortium, and the Faculty of Medicine Carl Gustav Carus, Technische Universität Dresden.